Frequency support strategy for single-Stage grid-Connected photovoltaic generation with active power reserves - Fu, Xuan; Wang, Xueying; Jia, Qi; Wang, Hongjiang (Frontiers in Energy Research, 2022)
Large-scale photovoltaic (PV) generation grid-connection will cause the lack of inertia and insufficient frequency regulation capacity of power system. To solve this problem, this paper proposes the active power-frequency droop control (APFDC) and virtual inertia control (VIC) for single-stage PV generation. PV power generation is able to participate the grid frequency regulation by improving the control system of voltage source inverter (VSC). The effect of control parameters on inertia characteristic of PV power generation is analyzed. On this basis, the distribution mechanism of unbalanced active power among PV generators with inertia control strategy is revealed. The simulation results indicated that the PV generation can be controlled by setting the control strategy of voltage source inverter (VSC) to reduce or increase the active power, and then take part in the frequency regulation of the system. Inertia provided by PV generation is controllable and frequency-dependent, increases with the increase of control gain, the decrease of time constant of virtual inertia control and the decrease of Phase-Locked Loop (PLL) control bandwidth.